ANALISIS SALURAN PEMASARAN PALA BANDA (Myristica fragrans Houtt) DI KECAMATAN BANDA NEIRA KABUPATEN MALUKU TENGAH - Marfin Lawalata (Agric, 2019)
Banda export nutmeg and mace commodities which are rich in essential oils make this plant one of the export commodities on the international market. Banda Neira with the sub-district center located on the island of Neira is one of the Districts in Central Maluku Regency which has the highest amount of nutmeg production, and is a natural spice of the Banda Islands and is known as the nutmeg Banda. This study aims to analyze the nutmeg marketing channel Banda in Banda Neira District, Central Maluku Regency. Sampling uses the random sampling method using a lottery. The data analysis method used is a quantitative analysis approach. The results showed that the in-depth knowledge of farmers about the handling of lean crops coupled with the discovery of aflatoxin which resulted in Banda nutmeg being rejected by international markets, this became a dilemma for exporters whose focus was on small farmers who in their post-harvest processing did not meet international quality standards. This is also triggered by the share received by farmers as the main marketing actor, which is much smaller than other marketing institutions that contribute to the Banda nutmeg marketing chain, so that handling and marketing seems not right, and strategies for more efficient marketing channel analysis are needed that is through the role of marketing institutions involved in developing and marketing nutmeg commodities. There was 70 percent of respondents (42 people) involved in the short marketing channel, through subdistrict traders and 30 percent (18 people) farmers engaged in the long marketing channel through village collectors with different levels of prices charged by each marketing agency.